High-Level Risk Analysis in the Construction Project of RSUD Dr. H. Slamet Martodirdjo in Pamekasan - Ridwan, Ridwan; Witjaksana, Budi; Purnama, Jaka (Pelopor Publikasi Akademika, 2025)
The construction of the Regional General Hospital Dr. H. Slamet Martodirdjo in Pamekasan Regency faces several challenges, particularly concerning high-level risks that may impact project success. This study aims to identify and analyze major risks affecting project completion and propose effective mitigation strategies. Using a survey method, data were collected from key stakeholders and processed using the Severity Index and Probability and Impact Matrix to assess risk levels. The findings identified 25 potential risks, with eight categorized as high-level risks: implementation method errors, difficulties in installing cross foundations, delays in critical path tasks, late material procurement, labor shortages, non-compliance with occupational safety regulations, lack of teamwork among workers, and adverse weather conditions. These risks significantly impact the project timeline, budget, and overall quality. The study also reveals that poor coordination among stakeholders, inefficient risk management practices, and regulatory constraints contribute to project delays. To mitigate these risks, strategic planning, improved procurement management, workforce training, and strict adherence to occupational safety regulations are recommended. Additionally, the adoption of technology-driven solutions, such as digital monitoring systems and e-procurement platforms, can enhance project oversight and efficiency. By implementing a systematic risk management framework, construction projects can minimize potential disruptions, ensure timely project delivery, and maintain cost efficiency. The findings of this study provide valuable insights for project managers, contractors, and policymakers in the construction industry, particularly for large-scale healthcare infrastructure projects. A proactive risk mitigation approach is essential to achieving successful project execution and sustainable infrastructure development.